THE HISTORICAL AND PHILOSOPHICAL ROLE OF SOCIAL CONSCIOUSNESS IN THE DEVELOPMENT OF CIVILIZATION - Kuchkorov, Javlon (Oriental Journal of History, Politics and Law, 2026)
This article analyzes the historical and philosophical role of social consciousness in the development of civilization. Social consciousness, as an important factor of social progress, has been formed throughout the historical development of humanity and has had a direct impact on civilizational changes. The study highlights the stages of formation of social consciousness, its philosophical essence, and its interrelation with the development of civilization.